(untitled) - Krentz, Jayne Ann (New York, 2020)
"From New York Times bestselling author Jayne Ann Krentz comes a new gripping romantic suspense trilogy fraught with danger and enigma. Decades ago in the small town of Fogg Lake, "The Incident" occurred: an explosion in the cave system that released unknown gases. The residents slept for two days. When they woke up they discovered that things had changed-they had changed. Some started having visions. Others heard ominous voices. And then the scientists from a mysterious government agency arrived. Determined not to become research subjects of strange experiments, the residents of Fogg Lake blamed the "hallucinations" on food poisoning, and the story worked. But now it has become apparent that the eerie effects of The Incident are showing up in the descendants of Fogg Lake... Catalina Lark and Olivia LeClair, best friends and co-owners of an investigation firm in Seattle, use what they call their "other sight" to help solve cases. When Olivia suddenly vanishes one night, Cat frantically begins the search for her friend. No one takes the disappearance seriously except Slate Arganbright, an agent from a shadowy organization known only as The Foundation, who shows up at her firm with a cryptic warning. A ruthless killer is hunting the only witnesses to a murder that occurred in the Fogg Lake caves fourteen years ago-Catalina and Olivia. And someone intends to make both women vanish"--
Kirkus Reviews
Publishers Weekly
Booklist
Library Journal
Adult
Keywords: Mystery fiction; Murder; Fiction; Missing persons; Fiction; romantic suspense novels; Romantic suspense fiction